Physicochemical Characteristics of Pempek During Boiling - Karneta, Railia; Kartina, Raida (Agrikan Jurnal Agribisnis Perikanan, 2023)
The numerical heat diffusivity model can be used to optimally predict the temperature and boiling time of pempek, because boiling affects the physicochemical characteristics of pempek lenjer. Apply the diffusivity model numerically to find the optimal temperature and boiling time for pempek and to see changes in the physicochemical properties of pempek during boiling, that will be achieved in this research. Research using Factorial RAK in 3 replications, the first factor is the ratio of dough in 4 levels and the other factors is the temperature of dough in 5 levels. The variables measured were determining the boiling time , saccharide analysis, amino acid analysis, texture, and pH . The results showed that fish-dominant pempek dough required a longer boiling time than tapioca flour-dominant dough. In fish-dominant pempek dough, the dextrin formed is higher but the maltose content is low , and high temperatures cause the dextrin content decreases but the maltose content increases. The dextrin content ranged from 43.056-16.497, and the maltose content ranged from 10.793 – 5.430. and high temperatures cause, the lower the amino acid content in water-soluble amino acids, but increased in water-insoluble amino acids. The dominant tapioca dough, and the high temperature, causes the texture and pH to also be high.Texture ranged from 315.133 gf - 803.00 gf, and the average pH ranged from 6.69 - 6.94.